Perception of peri’s image in russian poetry of the XIX century (the first article) - Yashina, Tatiana A.; Zhatkin, Dmitry N. (Universidade Estadual Paulista, 2021)
The article presents additions to the scientific research of D.N. Zhatkin and A.P. Dolgov «Peri in the Russian poetry», published in 2007 in the journal «Russian speech» and comprehending the facts that influenced the process of borrowing the image of Peri, which came from eastern mythology and appeared in the works of Russian writers and translators thanks to the reception of the works of Thomas Moore, namely one of his frame tales of Oriental Romance «LallaRookh» «Paradise and  the Peri». This article is the first to systematize materials on the topic, related to the works of M.Yu. Lermontov, N.A. Nekrasov, D.S. Merezhkovsky, A.P. Maikov, A.A. Fet, K.F. Ryleev; Russian poets created descriptions of women based on comparison with the symbolic image of the peri. The author analyzes the original poems of Russian poets dating back to the tradition of the Irish bard Thomas Moore, makes observations and generalizations.